TINJAUAN HUKUM TERHADAP PENGGUNAAN ALAT PEMBLOKIR IKLAN DI INDONESIA - Samudra, Muhammad Mpu (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
Advertisements are crucial for website sustainability, but intrusive, immoral, and virus-containing ads can hinder internet browsing. This has led to the emergence of ad-blockers that filter out problematic ads that users find annoying. This solution seeems effective. However, it is important to consider the legal regulation of electronic advertising in Indonesia and whether the use of ad-blockers is permitted by law. This research employs a normative juridical approach to address this issue. Based on the rule of law in Indonesia, the use of ad-blockers does not appear to violate the law. Users are free to block ads, but interfering with publishers' rights to deliver content in a way that they approve should be prohibited. However, these matters have not been regulated by Indonesian law. Keywords: Ad-blocker; Electronic Advertising; Intrusive Ads